So I've gotten into the Method of Frobenius and all; Solved a few questions, however the most inconvenient part would be the formulation of the general equations for the final answer. Granted, the lecturer told us to not spend so much time on that segment due to its minimal weightage, but I prefer to know. So, here's one which I am on and about right now; C_(k+1) = -2Ck/(k+1)(2k-1) k=0; C1= -2Co/(1)(-1) k=1; C2= -2C1/(2)(1) k=2; C3= -2C2/(3)(3) k=3; C4= -2C3/(4)(5) Their equivalant in terms of Co being -2Co/(1)(-1) (-2)^2 Co/(1)(-1)(2)(1) (-2)^3 Co/(1)(-1)(2)(1)(3)(3) (-2)^3 Co/(1)(-1)(2)(1)(3)(3)(4)(5) respectively. What I have tried doing was y= Co [Summation of](-2)^(n+1)/(n+1)!(<missing link>) I cannot complete it because I don't know any function that allows me to pile up previous values, so that the current will be multiplied by the previous. However, I am pretty sure that this isn't the correct method, so any help given will be very appriciated. Also, I would love to hear advice on what to look for when creating the general equation. Thank you.